2007
DOI: 10.1002/eji.200636588
|View full text |Cite
|
Sign up to set email alerts
|

The impact of HLA‐B micropolymorphism outside primary peptide anchor pockets on the CTL response to CMV

Abstract: The factors controlling epitope selection in the T cell response to persistent viruses are not fully understood, and we have examined this issue in the context of four HLA-B*35-binding peptides from the pp65 antigen of human cytomegalovirus, two of which are previously undescribed. Striking differences in the hierarchy of immunodominance between these four epitopes were observed in healthy virus carriers expressing HLA-B 195 . By comparing peptide-MHC association and disassociation rates with peptide immunog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 45 publications
3
35
0
Order By: Relevance
“…Although these experiments indicated that both the FPT and CPS epitopes bind to HLA B*3508 with equal efficiency, our recent studies have shown that the dissociation half-life for B*3508 CPS and B*3508 FPT complexes was 37.1 hours and 21.1 hours, respectively. 22 Taken together, these observations suggested the differences in the disassociation kinetics of the CPS and FPT epitopes for HLA B*3508 directly impacts on their antigen presentation efficiency in HCMV-infected cells, which was consistent with our previously documented evidence on the impact of pMHC binding on determinant selection. 27 …”
Section: Tcr Selection Correlates With Functional Properties Of Cps-asupporting
confidence: 91%
See 2 more Smart Citations
“…Although these experiments indicated that both the FPT and CPS epitopes bind to HLA B*3508 with equal efficiency, our recent studies have shown that the dissociation half-life for B*3508 CPS and B*3508 FPT complexes was 37.1 hours and 21.1 hours, respectively. 22 Taken together, these observations suggested the differences in the disassociation kinetics of the CPS and FPT epitopes for HLA B*3508 directly impacts on their antigen presentation efficiency in HCMV-infected cells, which was consistent with our previously documented evidence on the impact of pMHC binding on determinant selection. 27 …”
Section: Tcr Selection Correlates With Functional Properties Of Cps-asupporting
confidence: 91%
“…22 This is illustrated by HLA B35-restricted CD8 ϩ T-cell responses to the pp65 epitopes, CPSQEPMSIYVY and FPTKDVAL (herein referred to as CPS and FPT, respectively), which are exclusively recognized by HLA B*3508 ϩ individuals, while HLA B*3501 ϩ , HLA B*3503 ϩ , and HLA B35 Ϫ donors showed no significant ex vivo response to these epitopes ( Figure 1A). These observations were also confirmed by in vitro stimulation of T cells, which showed that these epitopes selectively expanded T cells from HLA B*3508 ϩ individuals ( Figure 1B).…”
Section: Cd8 ؉ T Cells Specific For Hcmv Epitopes Restricted Through mentioning
confidence: 99%
See 1 more Smart Citation
“…This has only been reported within a narrow slice of the Vβ repertoire, where consensus Vβ8.2 + CDR2β-mediated interactions were observed with closely related pMHC-II molecules (6,7). It is also suggested that the same V region can potentially interact with dis- (36), and RL16 (34,37). These experiments were independently performed twice for clones LC13, GL3, and CFB40, with analogous results on each occasion.…”
Section: Discussionmentioning
confidence: 82%
“…12 Clinically, HLA-B*44:02 and B*44:03 alleles are known to represent a non-permissive transplantation scenario 13 and are associated with strong alloreactive T-cell responses and acute graft-versus-host disease. Furthermore, substitutions at position 156 were demonstrated to modify T-cell alloreactivity in vitro for HLA-A2 subtypes [14][15][16] and HLA-B35 17,18 while polymorphism at this position also appears to be responsible for acute graft-versus-host disease in HLA-C mismatched donor-recipient pairs. 19 Position 156 is known to be one of the most non-permissive transplantation mismatches.…”
Section: Introductionmentioning
confidence: 99%